PowerCLI cookbook : over 75 step-by-step recipes to put PowerCLI into action for efficient administration of your virtual environment - Sellers, Philip (Quick answers to common problems., 2015)
If you are a virtualization professional who wants to unleash the power of automation and combat the complexity of sprawling virtual environments, this book is ideal for you. This book will enhance your skills of administering VMware vSphere and vCloud Director with PowerCLI.